HISTOPATHOLOGY KIDNEY OF Pangasisus hypopthalmus THAT ARE IMMERSED IN CURCUMIN AND WERE INFECTED BY Aeromonas hydrophila - Selvi, Novike Zullanda; Siagian, Morina Riauwaty; Syawal, Henni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study has been conducted on June to November 2015 in at Parasite and Fish Disease Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. The aims of this study was to determine the effect of curcumin extract from turmeric (Curcuma domestica Val) usage through the immersion method and infected by Aeromonas hydrophila on histopathological kidney of Pangasius hypopthalmus. This study used an experimental method and histological of the kidney structure of Pangasius hypophthalmus were analyzed by descriptive. The treated fishes were immerse in three different concentrations of curcumin extract. Kn: (Negative control) the fish were not immersed in Curcumin and without infected by Aeromonas hydrophila, Kp: (Positive control) were not immersed in Curcumin and were infected by Aeromonas hydrophila P1: The fish were immersed in curcumin 0,5 mg/L, P2: The fish were immersed in curcumin 0,7 mg/L, P3: The fish were immersed in curcumin 0,9 mg/L. The fish for two minutes for once a week and fishes were reared for 28 days. Showed that the abnormalities of kidney such us congestion, haemorrhage, degeneration , and necrosis. Base on data obtain it can be concluded that the best concentration of curcumin 0,9 mg/L is able to prevent the MAS disease in Aeromonas hydrophila.Key words : Pangasius hypopthalmus, curcumin extract, histopathology, kidney